The Biography of a Perfect Queen Addressed to an Imperfect Lady: The Life of Theodelinda of Bavaria in Giovanni Sabadino degli Arienti’s Gynevera de le clare donne - Rodríguez-Mesa, Francisco José (Renaissance and reformation, 2023)
Around 1489-90, during the period of his service for the house of Bentivoglio, Giovanni Sabadino degli Arienti wrote the Gynevera de le clare donne, a catalogue containing thirty-three lives of exemplary women, for Ginevra Sforza Bentivoglio, Giovanni II’s wife and counsellor. Even though throughout his work Sabadino insists on the virtues and perfection of his addressee, chroniclers wrote extensively about Ginevra’s cruelty, wrath, and vindictive personality as well as her unfaithfulness towards her first husband. Although all these features clearly contrast with the behaviours of the women included in the Gynevera, the perfection of the first of the protagonists of the book, Theodelinda of Bavaria, is constructed by Sabadino through allusion to a series of characteristics exactly opposed to those that the contemporary chroniclers attributed to Ginevra. In this article, I study Sabadino’s biography of Theodelinda as a paradigm of perfect woman and ruler, comparing it to the features that, according to fifteenth- and sixteenth-century chroniclers, made Ginevra Sforza Bentivoglio an imperfect wife and counsellor.